2009
DOI: 10.1592/phco.29.pt2.33s
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Liraglutide, a Long‐Acting, Potent Glucagon‐Like Peptide‐1 Analog

Abstract: Despite the continued development of new pharmacologic agents, and the use of several existing drug therapies, almost two thirds of patients with type 2 diabetes mellitus do not reach the American Diabetes Association-targeted hemoglobin A(1c) level of less than 7.0%. Therefore, maintaining adequate metabolic control remains a primary concern for many clinicians and patients. It is now well recognized that in addition to defective secretion and action of insulin, other hormones also potentially play a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
1
15
0
2
Order By: Relevance
“…Indeed, the PK profile of liraglutide and exendin-4 are quite different. In humans, levels of liraglutide are steadily maintained for ~24hr after injection, whereas exenatide levels rapidly peak and decline 10–12hr after injection, thus yielding more variation throughout the day (Meece, 2009). Regardless of these differences between the two drugs, it is the case that in most instances food intake suppression by the GLP-1R agonists does not occur without concomitant pica.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the PK profile of liraglutide and exendin-4 are quite different. In humans, levels of liraglutide are steadily maintained for ~24hr after injection, whereas exenatide levels rapidly peak and decline 10–12hr after injection, thus yielding more variation throughout the day (Meece, 2009). Regardless of these differences between the two drugs, it is the case that in most instances food intake suppression by the GLP-1R agonists does not occur without concomitant pica.…”
Section: Discussionmentioning
confidence: 99%
“…Greater weight reduction with liraglutide compared with sitagliptin can also be attributed to the mechanistic differences of GLP‐1 analogues and DPP‐4 inhibitors. Previous studies have shown that GLP‐1 receptor agonists increase satiety, reduce food intake and promote weight loss (13,14), whereas DPP‐4 inhibitors are generally weight‐neutral (3).…”
Section: Discussionmentioning
confidence: 99%
“…As stated, liraglutide is 97% homologous to the endogenous GLP‐1 hormone, with substitutions made at position 34 (replacing lysine with arginine) and a lipophilic moiety added to lysine at position 26 (a palmitic acid added through a glutamoyl spacer) . The prolonged activity of the molecule is achieved through self‐association because liraglutide forms heptamers in solution, as well as high plasma protein binding (more than 98%) and stability from degradation by the DPP‐4 enzyme . Bioavailability for subcutaneously administered liraglutide is ~55%, with similar absorption when administered in the abdomen, thigh, and upper arm .…”
Section: Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 99%